Polskie realia w kolędach i pastorałkach XVII i XVIII wieku (na materiale tzw. Kantyczek karmelitańskich) - Borejszo, Maria (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The object of research for the author of the article has been the ancient realities recorded in the texts of carols from the 17th and 18th centuries. The material originates from an extensive manuscript collection of Christmas carols and songs, comprising 357 texts, owned by the cloister of Carmelite nuns in Cracow. This invaluable written monument of religious lyric poetry was published in print by Barbara Krzyżaniak in 1980. The image of the world presented in the Old-Polish carols reflects – in a careful and detailed manner – the realities of the Baroque and the Enlightenment periods, especially the realities of poor Polish rural areas, which the authors of Christmas carols must have known firsthand. Specific saturation of Christmas songs with lay motifs can be observed in the central and closing part of the studied collection. In the lexicon found in Kantyczki karmelitańskie, which describes Old-Polish realities, two basic categories can be distinguished: one of them is composed of proper names (mainly the names and nicknames of shepherds and the names of nuns), the second – much more extensive and internally diversified – comprises the names of all kinds of objects that appear in the descriptions of shepherds’ preparations prior to their journey or merry-making at Christ’s crib. They are, for example, the information about the clothes worn by shepherds, farming implements and household objects, the means of transportation, foodstuffs, dishes, the animals reared or living free, the plants cultivated by people or growing naturally, musical instruments etc.